Update on obinutuzumab in the treatment of B-cell malignancies. (October 2014) - Illidge, Tim; Cheadle, Eleanor J; Donaghy, Claire; Honeychurch, Jamie
<x xml:space="preserve">Abstract</x> Introduction: The anti-CD20 mAb rituximab has revolutionized the treatment of B-cell malignancies, improving outcome for patients. Despite these improvements, the majority of patients still relapse and become refractory to rituximab. Further efforts to improve anti-CD20 mAb efficacy have recently focused on <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=obinutuzumab&logicalOpe1=OR&field2=articletitle&text2=obinutuzumab&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">obinutuzumab/GA101, a novel anti-CD20 mAb glycoengineered to display enhanced Fc-mediated effector mechanisms and induce direct cell death. Areas covered: We provide an overview of the current insights into the mechanisms of action of obinutuzumab focusing on how structural modifications and differences to rituximab led to designation of obinutuzumab as a type II antibody. We summarize data from preclinical studies and recent clinical trials including the Phase III trial in chronic lymphocytic leukemia (CLL), which led to FDA approval in November 2013. Expert opinion: Clinical data are now emerging confirming the promise of the initial preclinical data that demonstrated superior efficacy of obinutuzumab over rituximab at similar dosing. The emerging randomized Phase III data from older comorbid patients with previously untreated CLL demonstrated significant improvements in molecular remission rates and median progression-free survival of obinutuzumab plus chlorambucil versus rituximab plus chlorambucil. This emerging data provide reasons to be optimistic that outcomes for patients with B-cell malignancies can be further improved with obinutuzumab.